The Efficacy of Intraoperative Neurophysiological Monitoring to Detect Postoperative Neurological Deficits in Transforaminal Lumbar Interbody Fusion Surgery. Issue 1 (13th April 2018) - Kim, Joung Heon; Lenina, Svetlana; Mosley, Grace; Meaike, Joshua; Tran, Benjamin; Kim, Jun S; Cho, Samuel K
Abstract: BACKGROUND: Despite the extensive use of intraoperative neurophysiological monitoring (IONM) in spinal procedures, there is no standard guideline for what types of IONM tests should be monitored during lumbar procedures with instrumentation. Moreover, the efficacy of IONM during transforaminal lumbar interbody fusion (TLIF) surgery in detecting postoperative neurological deficits has not been well described. OBJECTIVE: To analyze waveform changes from individual IONM tests (somatosensory evoked potentials [SSEP], motor evoked potentials [MEP], and electromyography [EMG]) during TLIF and compare the sensitivity and specificity of these tests in order to determine the best combination to detect postoperative neurological deficits. METHODS: Two hundred seventy-five consecutive TLIF cases with IONM between 2010 and 2014 were reviewed, and new postoperative sensory and motor deficits were documented. Sensitivity and specificity for each IONM test in detecting postoperative sensory and/or motor deficits were analyzed. RESULTS: SSEP and EMG tests were performed on all 275 patients with 66 patients undergoing additional MEP tests. A total of 7 postoperative deficits have been reported: 2 sensory and 5 motor deficits. MEP test had high sensitivity (80.0%) and specificity (100%) in detecting motor deficits. However, SSEP changes failed to detect sensory deficits and EMG test had high false-positive rates for detecting both sensory (100%) and motor deficits (97.3%). CONCLUSION: MEP test should be incorporated in monitoring protocols during spinal procedures that involve instrumentations below vertebral level L1 such as TLIF, as it provides high sensitivity and specificity in detecting postoperative motor deficits. In addition, we propose modifying the standard lower extremity SSEP monitoring protocol to correspond to the vertebral levels being operated on.